2010
DOI: 10.1227/neu.0b013e3181f2b396
|View full text |Cite
|
Sign up to set email alerts
|

Early Draining Vein Occlusion After Gamma Knife Surgery for Arteriovenous Malformations

Abstract: Although venous structures are considered more radioresistant, endothelial damage accompanied by venous flow stasis might cause early venous thrombosis and premature venous occlusion after radiosurgery for AVMs. In our series, all patients had a favorable outcome except 1 with a fatal hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The early draining vein occlusion has been documented to occur at a range of 6.1 to 24.9 months (median, 11.6 months) after GKRS. 4 The shortest time gap between GKRS and occlusion of draining vein occlusion so far was reported by Celix et al, who reported a hemorrhage after GKRS after thrombus in the primary draining vein within 9 days after radiosurgery. 7 In the present case, our patient developed a neurologic deficit in 24 hours after GKRS because of thrombosis of the draining vein, which has not been reported previously in literature.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The early draining vein occlusion has been documented to occur at a range of 6.1 to 24.9 months (median, 11.6 months) after GKRS. 4 The shortest time gap between GKRS and occlusion of draining vein occlusion so far was reported by Celix et al, who reported a hemorrhage after GKRS after thrombus in the primary draining vein within 9 days after radiosurgery. 7 In the present case, our patient developed a neurologic deficit in 24 hours after GKRS because of thrombosis of the draining vein, which has not been reported previously in literature.…”
Section: Discussionmentioning
confidence: 97%
“…Most commonly, the obliteration process starts in the nidus and feeding arteries, and the draining veins close at the end. 4 It was considered that veins are more resistant to radiosurgery, as seen by poor response of venous angioma obliteration to radiosurgery. 5 However, Pollock described the interesting phenomenon of occlusive hyperemia wherein occlusion of draining vein occurred because of radiosurgery before the obliteration of AVM, which can lead to raised intracranial pressure, hemorrhage, or fresh neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although standard treatment of AVMs in both the surgical and radiosurgery arenas tend to advise sparing the draining vein, previous series with SRS to AVMs have not had as detailed visualization of draining veins as in our series, and it may be that in previous treatment plans the draining veins may have received an increased radiation dose compared to our treatments. Multiple series 51-54 have reported on patients developing radiation-induced changes surrounding the treated nidus and a concurrent thrombosis of the draining vein or veins. In these series, the majority of patients had a favorable outcome implying that some radiation to the draining veins may eventually help with AVM obliteration.…”
Section: Discussionmentioning
confidence: 99%
“…We did not use liquid embolic agent such as Onyx (eV3/Covidien, Irvine, CA) due to the eloquent location of the bAVM and due to the estimated risk of migration of the embolic agent into normal cortical branches related to reflux. We think that both corticosteroids 17 and embolization triggered the reduction of the edema and avoided the bleeding of the malformation.…”
Section: Physiopathologic Mechanismmentioning
confidence: 94%